A study of false alarm from CMS serving buildings - Tee, Siew Chong (1999)
Few things are more frightening to contemplate than a fire. Fires kill, destroy homes and leave survivors with painful, disfiguring injuries. Early warning of fire emergency is of utmost importance in order to save life and property. Fire Detection system plays a very important role and it can only be effective when there is no occurrence of false alarm. False Alarms disrupt production activities, office activities, sleep, etc. which lead to wastage of resources and it also demoralizes emergency crews (BOMBA/ERT) and building occupants from responding positively. In this paper, the objective is to carry out a study on the occurrence of false alarms in relation with human factor and automatic detector behavior according to day and night period within the week. Data was obtained from recorded eMS Bomba Link for a period of four months ie. June - September 1999 for twenty-one different buildings. The results indicate that the occurrence of false alarm happened during the daytime where working activities are in abundance. From observation ancl interview twenty-one buildings with maintenance and safety management, vandalism and excessive smoke/dust from working activities that may trigger the smoke detector are probably the two major causes of false alarm. If fire alarm sensor selection/maintenance is improved, it can reduce the frequency of false alarm very substantially and hence performs its intended purpose.